Does Digital Public Service Complaint Promote Accountability? A Comparative Analysis of Upik Yogyakarta and Qlue Jakarta - Dina Nurhidayati (Indonesian Association for Public Administration, 2019)
Public services provided by government have been an intensively researched topic. Not much literature addresses principle of accountability in digital public service innovation. This study aims to identify the extent which accountability can be promoted in the utilization of digital public complaints services, using descriptive qualitative methods with Bovens Model accountability function approach. In the form of a comparative study to compare unit of analysis as public service innovation handling digital based complaints UPIK and Qlue. The results of study were carried out after a comparison of accountability analysis, based on indicators of digital based public service accountability functions. The findings are: First, accountability influenced by four functions,(1)Democratic control,(2)Guarantees,(3)Learning, (4)Performance. Second, different periods of leadership influence the dynamics of accountability development. In conclusion, accountability function embedded by Qlue was being able to cutdown bureaucrats efficiently, in addition to the political system, leadership commitment and dynamic user existence. The quality of the UPIK system is still below Qlue, but UPIK's accountability capacity is more consistent in fulfilling the elements to promote accountability through effective complaints handling mechanisms. Not only more modern facilities, the performance of program that have supported by models and appropriate complaints handling mechanisms also capable of promoting accountable organizations.